Predictors of acute kidney injury in patients with acute decompensated heart failure upon admission at a cardiac intensive care unit. (3rd May 2023) - Carvalho, M; Goncalves, C; Cabral, M; Vazao, A; Lopes, S; Santos, L; Morais, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiorenal syndrome (CRS) type 1 is characterized as the development of acute kidney injury (AKI) and dysfunction in the patient with acute cardiac illness, most commonly acute decompensated heart failure (ADHF). Acute kidney injury (AKI) is associated with a worse overall prognosis in patients hospitalized with acute decompensated heart failure. Objective: To assess the predictors of AKI in patients with acute decompensated heart failure with reduced ejection fraction upon admission to the cardiac intensive care unit. Methods: A retrospective single-center observational study analyzed 105 patients admitted to a cardiac intensive care unit. between January 2022 and August 2022. The definition of AKI is based on KIDIGO (Kidney disease: Improving global outcomes). We compared clinical characteristics, echocardiographic parameters, selected biomarkers and outcomes between patients with and without AKI. A logistic regression analysis was performed, looking for independent predictors of AKI in this population. Results: Of the 105 patients, 45 (42.9%) presented with AKI. These patients were older (median age: 74 vs. 58 years, p=0, 009), lower body mass index (median: 26.4 vs.29.8 kg/m2, p=0, 038). Moreover, AKI was associated with an increased all-cause mortality rate and longer hospitalization. In addition, arterial hypertension (odds ratio [OR]: 1.69; 95% confidence interval [CI]: 1.25-2.57; p=0.015), age ≥ 73 years (OR 2, 1: 95% CI: 1.73-3.5, p=0, 036), previous diagnosis of coronary heart disease (OR 1.35: 95% CI: 1.0-2.2, p=0.021), diabetes mellitus (OR 1.27: 95% CI: 0.91-1.93, p=0.230), left ventricular ejection fraction <35% (OR 2.2: 95% CI 1.0-2.7, p=0, 003) at admission were significant predictors of AKI. Conclusion: This study suggests cardiovascular comorbidities, older age, lower ejection fraction were predictors of AKI in patients upon admission of patients hospitalized with ADHF in the cardiac intensive care unit.